Si-Tu. Tribal Hut / Constantine Claudius Embagos - Embagos, Constantine Claudius (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Derived from the Peselai migration of the Kenyah Tribe in virtue of the hanging sacrifies which leads to a search for haven. The Kenyah men practice headhunting and the women govern peace while having unique beauty preservation. SI-TU will serve as a hidden haven that offers a reminiscent of the tribe’s journey.